THE EFFECT OF WORK-LIFE BALANCE, ORGANISATIONAL CULTURE AND MOTIVATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION - Barokah, Muhammad; Suhardi, Suhardi; Sofyan, Agus; Amin, Mat (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyse the influence of Work-Life Balance (WLB), organisational culture, and work motivation on employee performance with job satisfaction as an intervening variable. The study was conducted on millennial employees in the local government of Pangkalpinang City, involving 104 respondents selected through a purposive sampling technique based on the criteria of having a minimum work period of one year, having permanent employee status, and being active in organisational activities. Using a quantitative approach with structural equation model analysis, the results showed that work motivation has a positive and significant effect on job satisfaction, while WLB and organisational culture have a positive but insignificant effect. This finding indicates that intrinsic factors, such as work motivation, play a more dominant role in shaping employee job satisfaction than external factors such as WLB and organisational culture. However, these three variables did not show a significant indirect effect on performance through job satisfaction. The practical implications of this study emphasise the importance of increasing work motivation through the development of reward and career systems, as well as the need to strengthen organisational culture and implement more effective WLB policies to create job satisfaction, which in turn can improve employee performance.